THE INFLUENCE OF COMPENSATION, WORK ENVIRONMENT, AND WORK INTEREST ON EMPLOYEE WORK MOTIVATION AT PT BANK CENTRAL ASIA (BCA) KCU RAWAMANGUN - Pragiwani, Meita; Narimawati, Umi; Suhardi, Yusuf; Sampurna, Dian Surya; No, Dhiu Stela (International Journal of Artificial Intelligence Research, 2024)
This research aims to determine the effect of compensation (X1), work environment (X2), and work interest (X3) on work motivation (Y) in PT Bank Central Asia (BCA) employees. The method used in this research is a quantitative method. Data was collected through a questionnaire which was measured using a Likert scale diagram. The sampling method used a purposive sampling technique totaling 70 respondents. This research is quantitative research using multiple linear analysis with the data analysis tool SPSS 23.The results of this research state that compensation has no effect on work motivation, the work environment has an effect on work motivation, and work interest has no effect on work motivation